OPTIMIZATION AND CHARACTERIZATION OF DOXORUBICIN LOADED SOLID LIPID NANOSUSPENSION FOR NOSE TO BRAIN DELIVERY USING DESIGN EXPERT SOFTWARE - SHAH, VIRAG A.; PATEL, JAYVADAN K. (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Objective: The goal of the current study was to investigate the possible use of solid lipid nanosuspension (SLNs) as a drug delivery method to boost doxorubicin (DOX) brain-targeting performance after intranasal (i. n.) administration. Methods: 33 factorial design was applied for optimization by using lipid concentration, surfactant concentration, and High-speed homogenizer (HSH) stirring time as dependent variables, and their effect was observed on particles size, Polydispersity index (PDI), and entrapment efficiency. Results: With the composition of Compritol® 888 ATO (4.6 % w/v), tween 80 (1.9 % w/v), and HSH stirring time, the optimized formula DOX-SLNs prepared (10 min). Particle size, PDI, zeta potential, entrapment efficiency, percent in vitro release were found to be 167.47±6.09 nm, 0.23±0.02, 24.1 mV, 75.3±2.79, and 89.35±3.27 percent in 24 h, respectively, for optimized formulation (V-O). No major changes in particle size, zeta potential, and entrapping efficiency were found in the stability studies at 4±2 °C (refrigerator) and 25±2 °C/60±5% RH up to 3 mo. Conclusion: Following the non-invasive nose-to-brain drug delivery, which is a promising therapeutic strategy, the positive findings confirmed the current optimized DOX-loaded SLNs formulation.